The grey king - Cooper, Susan, 1935-; Heslop, Michael (New York : Atheneum, 1975)
A strange boy and dog remind Will Stanton that he is an immortal, whose quest is to find the golden harp which will rouse others from a long slumber in the Welsh hills so they may prepare for the ultimate battle of Light versus Dark.
"A Margaret K. McElderry book."
G8
Keywords: Fantasy; Wales -- Fiction